Wearable Therapy – Detecting Information from Wearables and Mobiles that are Relevant to Clinical and Self-directed Therapy - Arnrich, Bert; Ersoy, Cem; Mayora, Oscar; Dey, Anind; Berthouze, Nadia; Kunze, Kai (Methods of Information in Medicine, 2017)
Background: This accompanying editorial provides a brief introduction into the focus theme “Wearable Therapy”.Objectives: The focus theme “Wearable Therapy” aims to present contributions which target wearable and mobile technologies to support clinical and self-directed therapy.Methods: A call for papers was announced to all participants of the “9th International Conference on Pervasive Computing Technologies for Healthcare” and was published in November 2015. A peer review process was conducted to select the papers for the focus theme.Results: Six papers were selected to be included in this focus theme. The paper topics cover a broad range including an approach to build a health informatics research program, a comprehensive literature review of self-quantification for health self-management, methods for affective state detection of informal care givers, social-aware handling of falls, smart shoes for supporting self-directed therapy of alcohol addicts, and reference information model for pervasive health systems.Conclusions: More empirical evidence is needed that confirms sustainable effects of employing wearable and mobile technology for clinical and self-directed therapy. Inconsistencies between different conceptual approaches need to be revealed in order to enable more systematic investigations and comparisons.
Keywords: Self-directed therapy; self-quantification; pervasive health; health self-management